Etymologi i monolingvale ordbøger - Kvaran, Guðrún (Nordiske Studier i Leksikografi, 2003)
The topic of this paper is etymological information in monolingual dictionaries. The examples used for demonstration are from several Scandinavian, German and English dictionaries that use different methods in explaining the history of the words, some of the dictionaries giving thorough information with reconstructed roots, but others only naming a few facts. At the end of the paper, the discussion turns to a method for etymological description in a monolingual Icelandic dictionary.